THE FUNCTION OF PLANT METAPHOR AS A SYMBOL OF UNITY FOR MANGGARAI SPEECH COMMUNITY - Fransiskus Bustan; Josua Bire; Agustinus Semiun; Hendrikus Jehane (Academic Journal of Educational Sciences, 2021)
This paper explores the function of plant metaphor as a symbol of unity for Manggarai speech community with special reference to the forms and meanings of the linguistic phenomena used in the plant metaphor. The study is descriptive. The study is viewed from cultural linguistics with special reference to metaphor as a part of cultural conceptualization emerging in cognitive level. The result of study shows that the form and meaning of plant metaphor as a symbol of unity for Manggarai speech society is reflected in the verbal expression, Muku ca pu’u neka woleng curup ‘One clump of bananas doesn’t talk differently, one clump of canes doesn’t walk differently’. The forms and meanings of the linguistic phenomena used in the plant metaphor are specific to Manggarai culture revealing the conceptualization of Manggarai speech community on the signifincance of maintaining unity in their contexts of living together as members of the wa’u as a patrilineal-genealogic clan. Besides contributing to the significance of cultural linguistics as an approach to exploring language differences due to cultural differences, the study is also beneficial to remind Manggarai speech community that the content stored in the plant metaphor implies local wisdom enherited from their ancestors that should be maintained and preserved.